Experimental studies on the performance and emission characteristics of an automobile engine fueled with fish oil methyl ester to reduce environmental pollution. (February 2019) - Prakash, S.; Prabhahar, M.; Sendilvelan, S.; Venkatesh, R.; Singh, Sanjay; Bhaskar, K.
Abstract: Transportation industry has become more relatively important as it has become an essential part of any economy, that propels the economic activity of a Nation, it has become essential to study the quality that should be made available to the users by this industry. Worldwide initiatives for cleaner production make it possible to increase the efficiency of the resources and controlling the release of pollutants to the air, water and land. The reuse of fish waste is a significant contributor to the overall environmental pollution. In this work, biodiesel obtained from fish wastes are used as alternative fuel to diesel in stationary diesel engines. Performance and emission tests of Fish Oil Methyl Ester (FOME) and their blends (80%, 60%, 40%, 20%) with diesel were carried out on a compression ignition engine at variable load conditions. The experimental results show that the carbon monoxide (CO), unburnt hydrocarbon (UBHC) and smoke emissions are less at all loads for the blends compared to diesel fuel while oxides of nitrogen (NOx ) emission alone is slightly higher. Trade-off between oxides of nitrogen and soot emissions for various percentage of FOME in blends show that 22% of FOME blend are observed to be optimum considering both NOx and soot emissions.